Preservation, conservation, and advocacy: a study of the Parktown Westcliff Heritage Trust (PWHT) in heritage management, 1965-2011 - Mutumi, Prue P.J. (My University, 2012)
This study is based on the Parktown Westcliff Heritage Trust (PWHT). The study focuses on the preservation, conservation and advocacy activities of the Trust in heritage management. It analyses how the Trust has managed to survive for over 40years and how it has adapted to the changes in legislation over time. Of particular salience, the study focuses on 3 historical moments in which the PWHT intervened to save buildings and landscapes from destruction. These moments span from 1965 to the present and they include the destruction of the Parktown Ridge from 1965 onwards, inner city-Newtown 1980 and the Beyers Naude Square in 2004. The moments selected for analysis, explore how the PWHT has managed to survive through two distinct political systems namely, apartheid and democracy. The analysis presented in this report draws attention to the application and interpretation of legislation and policy at both local and national levels in heritage management.
M.A. University of the Witwatersrand, Faculty of Humanities (Heritage), 2012
Keywords: Preservation; Advocacy; Heritage Management